2013
DOI: 10.1097/aln.0b013e31828744c0
|View full text |Cite
|
Sign up to set email alerts
|

Xenon and Isoflurane Reduce Left Ventricular Remodeling after Myocardial Infarction in the Rat

Abstract: Compared to isoflurane and s-ketamine, xenon limited progressive adverse cardiac remodeling and contractile dysfunction 28 days after perioperative myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
0
22
0
2
Order By: Relevance
“…The isoflurane may attenuate the deleterious effects caused by ventricular remodeling as demonstrated by Roehl and collaborators [66]. However, all animals underwent to the same anesthesia protocol being exposed to isoflurane for a short time, approximately 2 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The isoflurane may attenuate the deleterious effects caused by ventricular remodeling as demonstrated by Roehl and collaborators [66]. However, all animals underwent to the same anesthesia protocol being exposed to isoflurane for a short time, approximately 2 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Xenon has also been shown to protect isolated rabbit hearts from ischemia/reperfusion injury, 16 an effect that was abolished by the specific mitoK ATP channel blocker 5-hydroxydecanoate 16 . Along similar lines, xenon limits the mid-term ventricular remodeling triggered by myocardial infarction in neonate rats, resulting in improved contractility and increased ejection fraction 18 . Finally, xenon has been shown to reduce the renal allograft injury that is generally associated with prolonged hypothermic graft storage in multiple rat models of transplantation 4 , 19 , 20 .…”
Section: Resultsmentioning
confidence: 94%
“…Xenon has been shown to mediate prominent neuroprotective, 8 , 11 - 15 cardioprotective 16 - 18 and nephroprotective 4 , 19 , 20 effects in vivo. Thus, xenon protects the fetal brain in rat and piglet models of intrauterine perinatal asphyxia, a process that is accompanied by a significant reduction in neuronal apoptosis, 11 , 12 , 14 , 15 inhibits nitrous oxide- and isoflurane-induced neuronal death (and the consequent cognitive impairment) in newborn rats 13 and blunts the death of neurons triggered by the occlusion of the middle cerebral artery in rodents 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] In addition, in recent years, it was shown that xenon had neuroprotective, cardioprotective, and renoprotective effects in different animal models subjected to preconditioning, real-time conditioning, and postconditioning. [1417] However, the effects of xenon on respiratory function in patients with Stanford type A AAD during cardiopulmonary bypass (CPB) with DHCA remain unclear.…”
Section: Introductionmentioning
confidence: 99%